1998
DOI: 10.1598/rrq.33.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Everything You Wanted to Know About Phonics (But Were Afraid to Ask)

Abstract: The authors review basic principles underlying word learning and phonics instruction. These principles are applicable to many primary‐grade classrooms. They then discuss approaches to teaching phonics. Finally, they draw some tentative conclusions on how an integrated language arts program that includes phonics might look in a first‐grade classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 69 publications
1
51
0
2
Order By: Relevance
“…That and the fact that the little research available has been conducted by something other than disinterested parties (Stahl, Duffy-Hester, & Stahl, 1998). I am not surprised when someone, somewhere, manages to implement a program -any program -successfully.…”
Section: Looking Forwardmentioning
confidence: 99%
“…That and the fact that the little research available has been conducted by something other than disinterested parties (Stahl, Duffy-Hester, & Stahl, 1998). I am not surprised when someone, somewhere, manages to implement a program -any program -successfully.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Based on research that addresses the importance of phonics instruction in teaching children decoding skills (Adams, 1990;Chall, 1996;Stahl et al, 1998), the first hypothesis states that children who receive phonetic decoding instruction, regardless of the method of instruction (i.e., all children in the study), will show growth in word decoding, and will likely increase more in their decoding as the study progresses. This hypothesis was explored to determine the rate by which phonics instruction, in general, improves children's decoding skills.…”
Section: Hypothesesmentioning
confidence: 99%
“…Children should understand that all 26 symbols that make up the English alphabet are worth learning and discriminating because they each stand for sounds that occur in spoken words (Adams, 1990). Research has shown that early success in reading is associated with having an understanding of the alphabetic principle (Stahl, Duffy-Hester, & Doughtery, 1998).…”
Section: Phonicsmentioning
confidence: 99%
See 2 more Smart Citations